In silico identification of conserved intercoding sequences in Leishmania genomes: unraveling putative cis-regulatory elements. - Vasconcelos, Elton José Rosas de (2012)
Universidade de São Paulo. Faculdade de Medicina de Ribeirão Preto. Departamento de Biologia Celular e Molecular e Bioagentes Patogênicos. Ribeirão Preto, SP, Brazil